2007
DOI: 10.1097/00000542-200702000-00026
|View full text |Cite
|
Sign up to set email alerts
|

General Anesthetics and Vascular Smooth Muscle

Abstract: General anesthetics threaten cardiovascular stability by causing changes in cardiac function, vascular reactivity, and cardiovascular reflexes and significantly alter distribution of cardiac output to various organs. Their overall impact is often systemic hypotension, which is attributable to myocardial depression, peripheral vasodilation, and attenuated sympathetic nervous system activity. However, one could be more causative than the others, depending on anesthetic agents and cardiovascular factors inherent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 324 publications
(435 reference statements)
2
68
0
Order By: Relevance
“…Intravenous anesthetics are firmly established to have direct effects on vascular smooth muscle cells (VSMCs), resulting in modulation of blood pressure. For example, ketamine or midazolam reduces both intracellular Ca 2+ concentration ([Ca 2+ ]i) and myofilament Ca 2+ sensitivity, which leads to vasorelaxation [2]. Propofol reduces [Ca 2+ ]i via the protein kinase C (PKC)-dependent pathway, increasing guanosine 3', 5'-cyclic monophosphate (cGMP) or hyperpolarization of K + channel [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravenous anesthetics are firmly established to have direct effects on vascular smooth muscle cells (VSMCs), resulting in modulation of blood pressure. For example, ketamine or midazolam reduces both intracellular Ca 2+ concentration ([Ca 2+ ]i) and myofilament Ca 2+ sensitivity, which leads to vasorelaxation [2]. Propofol reduces [Ca 2+ ]i via the protein kinase C (PKC)-dependent pathway, increasing guanosine 3', 5'-cyclic monophosphate (cGMP) or hyperpolarization of K + channel [2].…”
Section: Introductionmentioning
confidence: 99%
“…For example, ketamine or midazolam reduces both intracellular Ca 2+ concentration ([Ca 2+ ]i) and myofilament Ca 2+ sensitivity, which leads to vasorelaxation [2]. Propofol reduces [Ca 2+ ]i via the protein kinase C (PKC)-dependent pathway, increasing guanosine 3', 5'-cyclic monophosphate (cGMP) or hyperpolarization of K + channel [2]. In our previous study [3], we have demonstrated that propofol inhibits endothelin-1-induced Ca 2+ influx and phosphoinositide-hydrolysis in VSMCs and the suppressive effect is exerted at the point between the receptors and heterotrimeric GTP-binding protein.…”
Section: Introductionmentioning
confidence: 99%
“…The calcium-dependent mechanism for vascular smooth muscle contraction is associated with a change in the concentration of cytosolic free calcium (Akata 2007). Calcium is mobilized from the sarcoplasmic reticulum and (or) the extracellular space to increase the cytosolic free calcium concentration, which stimulates the binding of calcium to calmodulin, leading to vasoconstriction (Akata 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, earlier studies have shown that propofol inhibited extracellular Ca 2+ -dependent responses to PGF 2a and KCL thereby suggesting that it may also inhibit receptor-operated calcium channel and voltage-operated calcium channel activities. 33 In contrast to its actions on KCl, BK, and PGF 2a , propofol does not reduce the vasoconstrictive effect of Ang II on human fetal placental circulation. This demonstrates that the mechanism of vasoconstrictor action of Ang II in the human fetal placental circulation is different at least in part from those of KCl, BK, and PGF 2a .…”
Section: Discussionmentioning
confidence: 94%
“…35 Finally, general anesthetics have been proposed to influence the myofilament Ca 2+ sensitivity of vascular smooth muscle cells in either the absence or presence of receptor stimulation. However, the underlying mechanisms are not well understood, 33 and possible alterations in myofilament Ca 2+ sensitivity by propofol in fetal placental circulation are not known.…”
Section: Discussionmentioning
confidence: 99%